2020
DOI: 10.3389/fphys.2020.556220
|View full text |Cite
|
Sign up to set email alerts
|

No Decrease in Blood Pressure After an Acute Bout of Intermittent Hyperpnea and Hypoxia in Prehypertensive Elderly

Abstract: Prevalence of hypertension, subjective sleep complaints and snoring increases with age. Worse sleep and snoring, in turn, are independent risk factors to develop hypertension. Both respiratory muscle training (RMT) and intermittent hypoxia (IH) are suggested to have positive effects on these physiological and behavioral variables. This study therefore aimed to test the acute effects of a single bout of RMT, with and without IH, on resting blood pressure (BP) and sleep. Fourteen prehypertensive elderly performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Responses may largely differ after one session of intermittent hypoxic exposure than after an entire protocol composed of several sessions. Only two studies investigated effect during and/or after one intermittent hypoxia in older individuals in association with cardiovascular outcomes [ 123 , 124 ]. Liu et al (2020) reported that the cerebrovascular response to hypoxia was diminished with age [ 123 ].…”
Section: Intermittent Hypoxia Conditioning - Targeting the Aging Card...mentioning
confidence: 99%
See 1 more Smart Citation
“…Responses may largely differ after one session of intermittent hypoxic exposure than after an entire protocol composed of several sessions. Only two studies investigated effect during and/or after one intermittent hypoxia in older individuals in association with cardiovascular outcomes [ 123 , 124 ]. Liu et al (2020) reported that the cerebrovascular response to hypoxia was diminished with age [ 123 ].…”
Section: Intermittent Hypoxia Conditioning - Targeting the Aging Card...mentioning
confidence: 99%
“…These findings confirm previous results showing a decreased cerebrovascular reactivity to hypoxia in older individuals, compared to young ones, during 5 min isocapnic hypoxic exposure [ 106 ]. Regarding blood pressure, no reduction was reported in pre-hypertensive older people after only one session of intermittent hypoxia [ 124 ]. However, in healthy older individuals, intermittent hypoxia reduced systolic blood pressure and diastolic blood pressure during the first and the last bout (5 bouts in total) of the first session [ 123 ].…”
Section: Intermittent Hypoxia Conditioning - Targeting the Aging Card...mentioning
confidence: 99%
“…An alternative form of exercise that does not involve lower or upper limbs and that can therefore be performed independently of mobility status is respiratory muscle endurance training (RMET). When RMET is performed at near maximal intensities, respiratory muscle O 2 consumption can account for up to 15% of whole-body maximal oxygen consumption (Aaron et al 1992), and average heart rate (HR) during a training session can increases to ~ 60% of predicted HR max in some individuals (Stutz et al 2020). Considering that brisk walking on level ground, which can elicit similar HR responses to RMET, has been shown to lower resting BP in elderly with systolic BP > 120 mmHg (Mandini et al 2018), one can argue that RMET intensity is sufficient to lower resting BP, but this remains to be tested.…”
Section: Introductionmentioning
confidence: 99%